The Influence of @Pevpearce Instagram Account on Dress Style - Dinda Oktaviani; Kukuh Sinduwiatmo (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to find out how the influence of Pevita Pearce on Instagram on Pevo's fashion style in Surabaya, the research uses quantitative methods. The location of this research was carried out by researchers on the Instagram account Pevo Surabaya with the duration of the study September 2020-November 2020. The research variables are social media and style. dress. The sample of this study was 100 respondents with a sampling technique that is simple random sampling. Data analysis used simple linear regression analysis. Based on the results of the analysis in the previous chapter, it can be concluded that the results of the data analysis test show that the influence of Instagram social media has a significant effect on the form of self-existence on changes in Pevo Surabaya fashion style. The influence of Instagram social media on Pevo Surabaya's fashion style is shown in the simple linear regression test table of 0.576 which can be categorized as high this is because Pevita herself is very active on Instagram and her fans gather on social media.